ANALYSIS OF DRINKING WATER QUALITY AND ENVIROTMENT HEALTH RISK OF IRON (Fe) POLLUTION FROM DUG WELLS IN THE WORKING AREA OF COMMUNITY HEALTH CENTER IN OGAN KOMERING ILIR REGENCY - Suryati, Eka; Maksuk, Maksuk (Perhimpunan Ahli Epidemiologi Indonesia, 2024)
Background: Iron is one of the metal parameters regulated in the Minister of Health's regulation regarding clean water and drinking water. Iron can cause health problems if it accumulates in the body.Methods: This study is a quantitative descriptive study with an environmental health risk analysis approach through a table-top approach evaluation to see the level of risk of heavy metal Fe in well water of residents in the working area of the Ogan Komering Ilir Regency Health Center. The study design is cross-sectional. This research was conducted in 2023 in the working area of the Ogan Komering Ilir Health Center. Results: Intake value based on the minimum Fe content in well water in adults were obtained at 0.00032 mg/kg/day, while in children it was 0.00070 mg/kg/day. The calculation results of the Fe Intake value based on the maximum Fe content in wells for adults were 0.00061 mg/kg/day while in children it was 0.00014 mg/kg/day. Meanwhile, based on the average value, the Intake value for adults was 0.00032 mg/kg/day, and for children it was 0.00070 mg/kg/day, with a Reference Concentration Dose of 0.3 mg/kg/day. The (RQ) value was obtained less than 1 for all calculations based on the intake value. Conclusion: The Fe levels in community well water in the Ogan Komering Ilir Community Health Center work area are still below the quality standard and the results of the Risk Quotient calculation in the water are still safe, but continuous monitoring by the Community Health Center is needed.